Comparison of methods for the identification of coagulase-negative staphylococci - Cunha, MLRS; Sinzato, Y. K.; Silveira, LVA (Fundaco Oswaldo Cruz, 2004)
Coagulase-negative staphylococci (CNS) species identification is still difficult for most clinical laboratories. The scheme proposed by Kloos and Schleifer and modified by Bannerman is the reference method used for the identification of staphylococcal species and subspecies; however, this method is relatively laborious for routine use since it requires the utilization of a large number of biochemical tests. The objective of the present study; was to compare four methods, i.e., the reference method, the API Staph system (bioMerieux) and two methods modifed from the reference method in our laboratory (simplified method and disk method), in the identification of 100 CNS strains. Compared to the reference method, the simplified method and disk method correctly identifed 100 and 99 % of the CNS species, respectively, while this rate was 84 % for the AN Staph system. Inaccurate identification by the API Staph method was observed for Staphylococcus epidermidis (2.2 %), S. hominis (25 %). S. haemolyticus (37.5 %). and S. warned (47.1 %). The simplified method using the simple identification scheme proposed in the present study was found to be efficient for all strains tested, with 100 % sensitivity and specificity and proved to be available alternative for the identification of staphylococci, offering, higher reliability and lower cost than the currently available commercial systems. This method would be very useful in clinical microbiology laboratory, especially in places with limited resources.
Keywords: coagulase-negative staphylococci; methods; identification; API Staph